Hemoperitoneum caused by spontaneous rupture of a leiomyoma: A case report - Michael McKendrick; Vinita Rajadurai; Jennifer Weishaupt; Venkata Kasina (Elsevier, 2024)
Uterine myomas, fibroids or leiomyomas are benign neoplasms that can present as abnormal uterine bleeding and pressure symptoms. Significant complications are infrequent, but they can be life-threatening. This is a case of a ruptured fibroid where excessive intra-abdominal bleeding resulted in hemoperitoneum. In this clinical scenario, timely recognition and intervention were essential to prevent morbidity and mortality.This article discusses the diagnostic challenges and surgical management of a case of hemoperitoneum resulting from spontaneous haemorrhage from a ruptured vessel on the surface of a subserosal leiomyoma.A 42-year-old patient with a known multi-fibroid uterus awaiting elective surgery presented with acute-onset abdominal pain to the emergency department. She had a distended, tender abdomen. Laboratory tests and contrast computerised tomography revealed haemorrhage with no clear source of bleeding. Emergency midline laparotomy revealed active bleeding from the surface of a posterior subserosal leiomyoma with 1950 mL hemoperitoneum. A total abdominal hysterectomy was performed, and the patient had an uncomplicated recovery.The pre-operative haemoglobin level was 80 g/L, which normalized after several blood transfusions. Histopathological examination confirmed multiple leiomyomas and haemorrhage associated with ischaemic changes.Hemoperitoneum from a bleeding degenerating leiomyoma is an exceedingly uncommon complication. The atypical presentation of abdominal pain and the presence of a multi-fibroid uterus posed diagnostic challenges. This case underscores the importance of considering leiomyomas as a potential cause of acute abdominal pain and bleeding. Timely surgical intervention, supported by a multidisciplinary approach, is essential for optimal patient outcome.